Enhancing Elementary Preservice Teachers’ Scientific Literacy by Using Flipped Problem-Based Learning Integrated with E-campus - Izzah Muyassaroh; Nur Luthfi Rizqa Herianingtyas (Graduate School of Universitas Negeri Malang, 2023)
This study aimed to enhance the elementary preservice teachers’ scientific literacy at Pelita Bangsa University by using flipped problem-based learning integrated with e-campus. This Classroom Action Research was done in three cycles and each cycle was conducted with planning, action, observation, and reflection stages. The subjects of this study were 32 preservice teachers in the elementary teacher education program of Pelita Bangsa University in the academic year 2021-2022. Instruments and data collection techniques were observation, questionnaire, and test. The result of this study showed that the implementation of flipped problem-based learning integrated with e-campus improved elementary preservice teachers’ scientific literacy.